Influence of Cruise Control Use on Vehicle´s Consumption - Loman Michal; Šarkan Branislav; Skrúcaný Tomáš (Logi, 2021)
Most vehicles used in road transport are powered by internal combustion engines. Depending on the nature of their operation, each vehicle releases a certain amount of emissions into the air. Among other things, emissions include carbon dioxide, which significantly contributes to the greenhouse effect. The quantity of CO2 produced is closely related to fuel consumption. The article presents the results of test drives which were performed on a passenger car meeting emission standard Euro 4. The aim of the study was to verify the impact of the use of cruise control on fuel consumption of the vehicle. The measurement was performed on the basis of test drives carried out on a highway section. The consumption was determined based on the data obtained from a diagnostic device, which was connected to the vehicle via OBD. The test drives were repeated several times in order to get as close as possible to the actual operation of the vehicle.